A meshless method for solving the time fractional advection–diffusion equation with variable coefficients. (1st January 2018) - Mardani, A.; Hooshmandasl, M.R.; Heydari, M.H.; Cattani, C.
Abstract: In this paper, an efficient and accurate meshless method is proposed for solving the time fractional advection–diffusion equation with variable coefficients which is based on the moving least square (MLS) approximation. In the proposed method, firstly the time fractional derivative is approximated by a finite difference scheme of order O ( ( δ t ) 2 − α ), 0 < α ≤ 1 and then the MLS approach is employed to approximate the spatial derivative where time fractional derivative is expressed in the Caputo sense. Also, the validity of the proposed method is investigated in error analysis discussion. The main aim is to show that the meshless method based on the MLS shape functions is highly appropriate for solving fractional partial differential equations (FPDEs) with variable coefficients. The efficiency and accuracy of the proposed method are verified by solving several examples.